Edmonton gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series. - Bonin-Labelle, Geneviève; Buddle, Kathleen; Carpenter, Les; Crazybull, Lauren; King, Gretchen; McMahon, Rob; Stonehouse, Jodi; Swain, Molly; Vowel, Chelsea; Quinn, Reuben (Université d'Ottawa | University of Ottawa, 2017)
A collection of documents, audio recordings, and programming resulting from the third gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series held in Edmonton on April 21st, 2017.
Keywords: First Nations; Inuit; Métis; Broadcasting; Podcasting; Radio; Policy; CRTC